ثنائية نمط الإسناد في الآيات القرآنية: Bitateral (predicatic) Pattern in the Quranic verses - د.عالية أكرم (JAR, 2023)
Bilateral Pattern Readings in The Quranic AyatA Nominative Noun – in the case of Ishtighal – is converted to an Accusative Noun, & the Nominal Sentence to a Verbal Sentence. The change in the specific I’rab(إعراب) is reflected on nouns in the Quranic Readings, giving a variety of meanings to the Ayat of the Holy Quran. The term I’rab(إعراب) reflects a specific case that every noun carries. Specifically, it is a characteristic that imports the noun to have certain grammatical function(s). Every noun carries one of three cases. The default case of a noun is a Raf state, e.g. only nouns in the Raf I’rab can function as the subject in a Nominal Sentence. Likewise, the “Doer “can only be Raf in a verbal sentence. By contrast, only a noun in the Nasb I’rab can function as an object of a verb in a verbal sentence. The Specific I’rab is reflected on nouns by the varying vowels at their ends